USE AND ABUSE OF THE SERVICE OF THE “INDIGENOUS ATALAYEROS” IN NOVOHISPANO YUCATAN (Tzintzun, Revista de Estudios Históricos, 2016)
The work of the “indigenous atalayeros”, which is reported from the firstyears of the Colonial times in Yucatan, appears primarily with thecharacteristics of a personal service, although later it is hidden like a benefitto the king, and later on like a public load. However, at anyone of thedenominations it hid in an open way the usufruct that was made of thework of the natives. This distribution service has not been considered up tonow in the studies of the personal service in Mexico.
Keywords: Atalayeros; vigia; personal service; Colonial Yucatan; ilegal trade